Peran RADEC dalam Mengembangkan Kreativitas dan Pemahaman Konsep Siswa Kelas V pada Materi Pertumbuhan Manusia - Tias Siti Nurafifah; Atep Sujana; Ani Nur Aeni (Postgraduate, University of Mataram, 2024)
This research is based on the low level of creativity and conceptual understanding of grade 5 elementary school students, due to a lack of variety in learning. Students' creativity and understanding of concepts need to be developed through the implementation of RADEC learning. This research aims to determine the role of RADEC learning in developing fifth grade students' creativity and understanding of concepts in human growth material. The research method used was quasi-experimental with a pretest-posttest nonequivalent control group design. The research subjects were Class V students in one of the elementary schools in West Bandung Regency. Data collection techniques use tests and non-tests. The data is explained in detail through descriptive analysis, with non-parametric tests via the Kendalls' W test for creativity data and prerequisite and parametric tests for concept understanding results. The results of this research show that the Kendall's W test result of 0.92 shows that there is a high level of agreement between the 3 judges regarding the products that have been made by the students. The results of the mean rank of experimental class products show the top 4 rankings of the 8 products evaluated. The average N-Gain of students' conceptual understanding in the experimental and control classes was 0.72 and 0.31 in the high and medium categories. Therefore, it can be concluded that RADEC learning plays a positive role in developing students' creativity and understanding of concepts in human growth material.